1996
DOI: 10.2135/cropsci1996.0011183x0036000400052x
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Manokin’ Soybean

Abstract: Registration of 'Manokin' Soybean 'Manokin' soybean [Glycine max (L.) Merr.] (Reg. no. CV-347, P1 559932) was developed by the Maryland Agricultural Experiment Station. Itwas jointly released in 1991 with the Arkansas, Missouri, Oklahoma, andVirginiaAgriculturalExperimentStations. Manokin was released because of its superior yield compared with cultivars of similar maturity and its resistance to soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) derived from Peking. Manokin originated as an F4-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…The gradual increase in solution salinity over this period was designed to prevent a sudden osmotic shock to the soybean seedlings. of these salinity levels was based on previous experience with salt tolerance of the "Manokin" soybean (Kenworthy et al, 1996;Wang et al, 2001;Grieve et al, 2003). Solution osmotic potential and concentrations of the salinizing salts (Ca 2+ , Mg 2+ , Na + , SO 2− 4 , Cl − ) are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The gradual increase in solution salinity over this period was designed to prevent a sudden osmotic shock to the soybean seedlings. of these salinity levels was based on previous experience with salt tolerance of the "Manokin" soybean (Kenworthy et al, 1996;Wang et al, 2001;Grieve et al, 2003). Solution osmotic potential and concentrations of the salinizing salts (Ca 2+ , Mg 2+ , Na + , SO 2− 4 , Cl − ) are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Cultivars "Manokin" and "Essex" were used in these experiments. "Essex" has been classified as a Cl accumulator (Yang and Blanchar 1993), while "Manokin" has salt tolerance similar to "Lee" (Kenworthy et al 1996), a chloride excluder (Maftoun et al 1982). Previous research has indicated that "Essex" metabolizes chlorimuron rapidly and is relatively tolerant to chlorimuron (Moseley, Hatzios, and Hagood 1993).…”
Section: Seedsmentioning
confidence: 99%
“…DP3589 is a sib of ‘DP3588’ (Shannon and Collins, 2001). J00‐2 is an experimental line derived from ‘Manokin’ (Kenworthy et al, 1996) × ‘Fowler’ (Young, 2001) developed by Dr. Lawrence D. Young, ARS, Jackson, TN (personal communication, 2012).…”
Section: Methodsmentioning
confidence: 99%